The Role of Whole-Body MRI in Oncology: Current Status and Future Trends (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Whole-body magnetic resonance imaging (WB-MRI) has emerged as a powerful, non-ionizing modality for the comprehensive assessment of oncologic patients. Its ability to provide a holistic view of the body's soft tissues, bone marrow, and organs in a single examination positions it uniquely for cancer staging, restaging, and screening in high-risk populations. This review delineates the current evidence-based applications of WB-MRI across various malignancies, highlighting its superior sensitivity for bone metastasis detection and its growing role in response assessment. We detail the technical underpinnings of modern WB-MRI protocols, including diffusion-weighted imaging (DWI), which serves as a functional biomarker for tumor cellularity. Furthermore, we explore the burgeoning trends poised to redefine its utility, including the integration of artificial intelligence (AI) for accelerated acquisition and automated analysis, the development of whole-body PET/MRI systems, and the exploration of novel quantitative biomarkers. Despite challenges related to standardization, access, and cost, WB-MRI is increasingly recognized as a cornerstone of precision oncology, offering a safe and comprehensive diagnostic pathway.